Pengaruh Lingkungan Kerja Non-Fisik dan Konflik Peran terhadap Turnover intention Pengurus Pondok Pesantren - Muhammad Irsyad Al Asna; Agus Frianto (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Turnover intention among administrators of Islamic boarding schools has become an important issue in human resource management, particularly within institutions that emphasize service, spirituality, and organizational commitment. Previous studies have reported inconsistent findings regarding the influence of the non-physical work environment on Turnover intention, while empirical evidence from pesantren settings remains limited. In the context of Pondok Pesantren Madrasatul Quran Tebuireng, administrators frequently experience multiple role demands as students, educators, and organizational managers, creating potential role conflict that may affect their intention to leave the organization. Using an associative quantitative approach, data were collected from all 65 administrators through a saturated sampling technique and analyzed using multiple linear regression. The findings indicate that the non-physical work environment has a significant negative effect on Turnover intention, whereas role conflict has a significant positive effect. Simultaneously, both variables significantly influence Turnover intention. The results reveal that supportive interpersonal relationships, effective communication, and a conducive psychosocial environment contribute to reducing the intention to leave, while competing responsibilities and overlapping demands increase withdrawal tendencies. The study contributes to the literature by demonstrating that the relationship between work environment, role conflict, and Turnover intention in pesantren organizations is shaped by distinctive spiritual values and a culture of khidmah, which may restrain administrators from translating Turnover intention into actual resignation decisions.